The Clinical and Economic Burden of Idiopathic Hypersomnia: Results from the Real-World Idiopathic Hypersomnia Total Health Model (RHYTHM) Study - Saad R; Markt SC; Lillaney P; Profant DA; Fuller DS; Poole EM; Alvord T; Prince P; Desai S; Whalen M; Ni W; Black J (Nature and Science of Sleep)
Ragy Saad,1 Sarah C Markt,1 Prasheel Lillaney,1 Deb A Profant,1 Douglas S Fuller,2 Elizabeth M Poole,1 Trevor Alvord,3 Patricia Prince,3 Shaina Desai,3 Marisa Whalen,2 Weiyi Ni,1 Jed Black1,4 1Jazz Pharmaceuticals, Palo Alto, CA, USA; 2Jazz Pharmaceuticals, Philadelphia, PA, USA; 3Aetion, Inc, New York, NY, USA; 4Stanford University Center for Sleep Sciences and Medicine, Palo Alto, CA, USACorrespondence: Jed Black, Stanford University Center for Sleep Sciences and Medicine, 401 Quarry Road, #3301, Palo Alto, CA, 94304, USA, Email jed.black@jazzpharma.comPurpose: Limited research describes the clinical and economic burden of idiopathic hypersomnia. This study compared this burden in individuals with idiopathic hypersomnia against matched controls.Patients and Methods: This retrospective cohort study analyzed Merative™ MarketScan® US claims (12/31/2013– 2/29/2020). Individuals were ≥ 18 years of age and continuously enrolled during a 2-year assessment period. Individuals with idiopathic hypersomnia entered the cohort upon their first idiopathic hypersomnia medical claim; they were matched 1:5 with non–idiopathic hypersomnia controls on age, sex, region, insurance type, and cohort entry date. Odds of comorbid conditions experienced by individuals in either cohort during the 2-year assessment were compared. Healthcare resource utilization (HCRU) was presented as percentages by care setting. Median medical cost per patient per year (PPPY) was the sum of inpatient, outpatient, and emergency costs. P-values were not adjusted for multiplicity.Results: This analysis included 11,412 individuals with idiopathic hypersomnia and 57,058 matched controls. In both cohorts, median age was 45 years and 65% of individuals were female. Compared with matched controls, individuals with idiopathic hypersomnia had 1.6- to 4.4-fold higher odds (all P< 0.0001) of grouped conditions defined by multilevel Clinical Classifications Software categories, from neoplasms to nervous systems diseases, including sleep-related conditions. Individuals with idiopathic hypersomnia had higher odds of all comorbid conditions evaluated, including sleep-related, cardiovascular and cardiometabolic, and neuropsychiatric conditions, compared with matched controls. Individuals with idiopathic hypersomnia had higher HCRU (outpatient, 100% vs 96.1%; emergency department, 46.6% vs 34.3%; inpatient, 10.2% vs 8.5%, all P< 0.0001) than matched controls. Median medical costs PPPY were higher for individuals with idiopathic hypersomnia ($4854) than matched controls ($1348).Conclusion: Compared with matched controls, individuals with idiopathic hypersomnia had a higher clinical burden, spanning multiple organ systems, and a higher economic burden. Individuals’ clinical profiles may be considered when treating idiopathic hypersomnia and providing holistic care.Plain Language Summary: Idiopathic hypersomnia is a rare sleep disorder that can impact quality of life, work, and overall wellbeing. People with this sleep disorder are often excessively sleepy throughout the day and can sleep for over 11 hours a day. This study aimed to learn about other conditions that people with idiopathic hypersomnia are likely to have, how often they go to the doctor, and how much their healthcare costs. The study compared people with and without idiopathic hypersomnia. To compare these 2 groups, healthcare claims data (medical bill information) were used. Each person with idiopathic hypersomnia was compared with 1 or more (up to 5) people without idiopathic hypersomnia who were similar in characteristics such as age, sex, where they lived, and their type of health insurance. The study found that people with idiopathic hypersomnia are more likely to have other medical conditions, such as brain and nerve diseases, heart-related diseases, and mental illnesses; see their doctors more often; and have higher medical costs than people without idiopathic hypersomnia. These results are important because they raise awareness around the hardship faced by people who have this rare sleep disorder and help doctors understand their needs. Keywords: sleep–wake disorders, comorbid conditions, cohort studies, retrospective studies, healthcare resource utilization, healthcare costs